Giant magnetoresistance ratio in a current-perpendicular-to-plane spin valve based on an inverse Heusler alloy Ti2NiAl - Feng, Yu; Cui, Zhou; Wu, Bo; Li, Jianwei; Yuan, Hongkuan; Chen, Hong (Beilstein Journal of Nanotechnology, 2019)
A Ti2NiAl inverse Heusler alloy based current-perpendicular-to-plane (CPP) spin valve (SV) with various kinds of atomic terminated interfaces has been designed to explore the potential application of Heusler alloys in spintronics devices. By performing first principles calculations combined with the nonequilibrium Green’s function, it is revealed that spin magnetic moments of interfacial atoms suffer a decrease, and the electronic structure shows that the TiNiB-terminated structure possesses the largest interface spin polarization of ≈55%. Our study on spin-transport properties indicates that the total transmission coefficient at the Fermi level mainly comes from the contribution from the spin up electrons, which are regarded as the majority of the spin electrons. When the two electrodes of the CPP-SV device are in parallel magnetization configuration, the interface containing Ti and Ni atoms possesses a higher spin up transmission coefficient than the interface containing Ti and Al atoms. The device with the TiNiB-terminated interface possesses the largest magnetoresistance ratio of 3.28 × 105, and it has great application potential in spintronics devices.
Keywords: current-perpendicular-to-plane geometry; Heusler alloy; nonequilibrium Green’s function; spin transport; spintronics; spin valve